Designing calm and non-intrusive ambient assisted living system for monitoring nighttime wanderings. Issue 2 (5th June 2017) - Radziszewski, Robert; Ngankam, Hubert Kenfack; Grégoire, Vincent; Lorrain, Dominique; Pigot, Hélène; Giroux, Sylvain
Abstract : Purpose: Assistive living technologies provide support for specific activities, transforming a home into a smart home. The purpose of this paper is to present how to design, implement, deploy and install a personalized ambient support system for the elderly suffering from Alzheimer's disease (AD) and nighttime wandering. Design/methodology/approach: The intervention presented in this paper proceeds in two phases. During the monitoring phase, the system determines the profile of the person with AD, based on nighttime routines. Data are gathered from sensors dispatched in the smart home, coupled with physiological data obtained from sensors worn by the person. Data are then classified to determine engine rules that will provide assistance to the resident to satisfy their needs. During the second phase, smart assistance is provided to the person via environmental cues by triggering rules based on the person's habits and the activities occurring during night. Findings: The paper develops the architecture of a non-intrusive system that integrates heterogeneous technologies to provide a calm environment during night and limit wandering periods. Practical implications: The goal is to help people age well at home as long as possible and recover a regular circadian cycle while providing more comfort to the caregiver. Originality/value: The system presented in this paper offers a calm and personalized environment with music and visual icons to soothe persons with AD and encourage them to go back to bed. It is installed at the patient's home using wireless technologies.